A uniform survey of allele-specific binding and expression over 1000-Genomes-Project individuals - Jieming Chen (Nature Portfolio, 2016)
Using variants from the 1000 Genomes Project, RNA-seq and ChIP-seq data from related projects, this study describes a resource and survey of allele-specific binding and gene expression. A catalogue of allelic SNPs and annotation elements is available as an online resource at alleledb.gersteinlab.org.